The costs of corruption to the Mozambican economy. Why it is important to fight corruption in a climate of fiscal fragility - CIP and CMI (Centro de Integridade Pública (CIP) and Chr. Michelsen Institute, 2016)
What is the price that Mozambique has to pay for the widespread corruption in the country? What is the cost of corruption for the...
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Pobreza e Bem-Estar em Moçambique: Quarta Availação Nacional - Inquérito Ao Orçamento Familiar - Iof 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Pobreza e Bem-estar em Moçambique: Resumo da Quarta Availação Nacional - Inquérito ao Orçamento Familiar - IOF 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Country Evaluation Brief - Mozambique - CMI (Chr. Michelsens Institutt (CMI), 2016)
The purpose of this Country Evaluation Brief is to present relevant knowledge about donors’ development efforts in Mozambique. The brief systematises relevant findings from existing evaluations of development interventions in the country. The idea is to present the findings to the reader in a succinct and easily accessible format
ISBN 978-82-7548-840-2
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação

Mozambique: Report 8/2016 Country Evaluation Brief - Tvedten, Inge; Orre, Aslak (Norwegian Agency for Development Cooperation (Norad), 2016)
The purpose of this Country Evaluation Brief is to present relevant knowledge about donors’ development efforts in Mozambique. The brief systematises relevant findings from existing evaluations of development interventions in the country. The idea is to present the findings to the reader in a succinct and easily accessible format.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Poverty and Well-Being in Mozambique: Fourth National Poverty Assessment - Ministry of Economics and Finance (Ministry of Economics and Finance - Directorate of Economic and Financial Studies, 2016)
This report provides a comprehensive analysis of poverty and well-being, including temporal trends, in Mozambique. It is based on the 2014/15 household budget survey data (Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15), conducted by the National Statistics Institute (Instituto Nacional de Estatística, INE). Results from this latest survey are compared to those obtained in previous survey rounds (2008/09, 2002/03 and 1996/97). We consider poverty and well-being across an array of dimensions and using two principal approaches. The first approach focuses on consumption allowing assessment of progress towards the Millennium Development Goals. The second principal approach relies on multidimensional methods for assessing poverty and well-being. The indicators employed are drawn from the four household budget surveys. They relate to education, health, housing, and possession of durable goods.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; economic development / desenvolvimento económico; poverty / pobreza

Government Decentralization Program in Indonesia - Nasution, Anwar (Asian Development Bank Institute, 2016)
Without much preparation, Indonesia, in 2000, at a stroke replaced the previous system of centralized government and development planning with a wide range of decentralization programs. The reforms gave greater authority, political power, and financial resources directly to regencies and municipalities, bypassing the provinces. The powers transferred include those of executing a wide range of responsibilities in the areas of health, primary and middle-level education, public works, environment, communication, transport, agriculture, manufacturing, and other economic sectors. At the same time, the government replaced the antiquated cash-based, single-entry system of public finance with a modern double-entry accounting system that uses a single treasury account; is performance based; and has transparent management of the public treasury, tight expenditure and financial controls with performance indicators, computerized reporting, and a tightly scheduled auditing system.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Análise do desenvolvimento institucional do processo de descentralização em Moçambique: lógicas e dinâmicas políticas - Rosário, Domingos Manuel do (Instituto de Estudos Sociais e Económicos (IESE), 2016)
Moçambique é uma colónia portuguesa antiga, que alcançou a independência em 1975, depois da queda do regime fascista português em Abril de 1974. O sucesso militar da Frelimo contra os portugueses, deu legitimidade a este movimento para se impor como o único representante da sociedade (Cahen, 2003). Em 1977, o Comité Central da Frelimo realizou o 3° congresso que marcou oficialmente a passagem ao partido Marxista-leninista e de «Vanguarda». A partir de 1980, o campo político Moçambicano foi objecto de uma série de transformações. Em 1983 assistimos a realização do IV congresso da Frelimo que recomendou o governo a operar reformas económicas e administrativas que iniciaram em 1987. Estas reformas culminaram com a aprovação em 1990 de uma Constituição pluralista que estabeleceu “liberdades políticas”. Em 1992 o governo da Frelimo e o movimento de guerrilha da Resistência Nacional de Moçambique (Renamo) assinaram o Acordo Geral de Paz em Roma que pôs fim a uma guerra civil, que durante 16 anos (1976-1992) devastou o tecido social, económico e político do país. Em Setembro de 1994 a Assembleia popular aprovou por unanimidade a Lei 3/1994 - Programa dos órgãos locais do Estado; e finalmente a 4 de Outubro de 1994 realizaram-se as primeiras Eleições Gerais multipartidárias em Moçambique. As eleições Gerais Presidenciais e Legislativas de 1994 foram ganhas pela Frelimo (44,33%) e seu candidato Joaquim Chissano (53,30%) contra 33,73% de Afonso Dhlakama e 37,78% da Renamo (STAE, 1997). Em resultado do processo de colonização e das políticas implementadas pela Frelimo durante o período do Marxismo-leninismo foi possível observar dois fenómenos nestas eleições: A clivagem étnico-regional e a clivagem rural-urbano. A Frelimo conseguiu grandes maiorias nos centros urbanos e nas regiões sul (Maputo, Gaza e Inhambane) e no extremo Norte (Cabo Delgado). É destes meios que é oriunda a elite assimilada e intelectual (sul) e militar (Cabo Delgado). A Renamo saiu vitoriosa nas zonas rurais das províncias do Centro (Manica, Sofala e Tete), Centro Nordeste e Norte (Zambézia e Nampula respectivamente). A Frelimo conquistou 59% do total dos votos urbanos contra apenas 29% da Renamo. Por sua vez, a Renamo ganhou 41% do total dos votos rurais, contra 40% da Frelimo (Brito, 1995). Apesar do aparecimento do Movimento Democrático de Moçambique (MDM) no cenário político nacional a partir de 2009, a estrutura do voto produzida nas eleições de 1994 permanece inalterável até hoje. A Frelimo se sentindo ameaçada pela legitimidade democrática ganha pela Renamo, nas eleições de 1994 inicia um processo de reconstrução do Estado e da economia a seu favor (Sumich & Honwana, 2007). Na ausência de uma política e Estratégia de Descentralização (entretanto aprovada em 2012), a Frelimo optou por um compromisso misto de desconcentração: descentralização com eleições para as zonas urbanas/municípios - com a substituição da Lei 3/1994 pela Lei 2/97 das autarquias locais; e uma descentralização sem eleições para as lideranças dos distritos e das províncias - com a aprovação da Lei 8/2003 - Lei dos órgãos locais do Estado (LOLE). Esta descentralização foi concebida como meio para construir ligações significativas e duradouras entre o partido - Estado até então altamente centralizado e os cidadãos, ligações essas que tinham sido seriamente desafiadas, se não quebradas durante a guerra (Weimer, 2012).
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização

Reality checks in Mozambique – Building better understanding of the dynamics of poverty and well-being. Year Five, 2015, Sub-Report, District of Lago. - Tvedten, Inge; Putile, Beatriz; José, Barnabé; Paulo, Margarida (ORGUT Consulting AB, 2016)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 5th Sub-Report from the District of Lago, focussing on quantitative expressions of changes in poverty and wellbeing and the role of public institutions since the 1st Reality Check in 2011. An Annual Report is produced each year to summarise the findings and conclusions from the three subreports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Mozambique: Growth Corridors - ARUP (Arup and Cities Alliance, 2016)
This report relates to urbanisation as it is currently happening in Mozambique. It explores the present situation of cities and the government’s planned urbanisation strategy. It also discusses how the country plans to transition to a majority urban population. The report also discusses the impact of the urbanisation strategy on the regional development of the country through the promotion of growth corridors. To discuss this message, Future Cities Africa has selected three cities along the Nacala Corridor - Tete, Nampula, and Nacala - to explore current urbanisation trends and to highlight key challenges these cities may face in the future. This report relates to urban growth corridors in Mozambique and represents one of four reports prepared for Future Cities Africa. Each report covers a specific country, its national urbanisation strategy and its specific regional planning typology. The other three reports include metropolitan cities in Ghana, secondary cities in Uganda, and regional cities in Ethiopia
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; urbanization / urbanização

Civil society organisations’ political control over Brazil and Japan’s development cooperation in Mozambique: More than a mere whim? - Chichava, Sérgio; Durán, Jimena (LSE, 2016)
This article aims to analyse and explain the reasons behind the CSOs’ strong criticism of the ProSavana programme. This will contribute toward: (1) understanding the role of Mozambican CSOs as actors regulating international development cooperation projects; (2) revealing the political and economic interests behind ProSavana, as a first step toward a more critical approach to trilateral cooperation; and (3) illustrating through this case how a partnership between Brazil and “traditional” donors actually works. Firstly, we will analyse the cooperation policies of Brazil and Japan in Mozambique, taking into account its evolution, actors, mechanisms and motives. Secondly, we will introduce ProSavana, examining the narratives and roles of Japan and Brazil in this programme. Thirdly, we will consider the engagement of CSOs from the three countries, their role in exerting a political check on the Brazilian and Japanese governments, investors, and companies, as well as their narratives and mechanisms of protest.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; civil society / sociedade civil; development partners / parceiros de cooperação

Porquê o conflito armado em Moçambique? Enquadramento teórico, dominância e dinâmica de recrutamento nos partidos da oposição - Cortês, Emmanuel de Oliveira (2016)
A partir de um modelo de previsões sobre dominância e a dinâmica de recrutamento nos partidos da oposição em sistemas de partido dominante, pretendeu-se perceber as dinâmicas do conflito político em Moçambique que culminaram com o agravamento da tensão militar entre as forças armadas do Governo moçambicano, e o maior partido da oposição, a RENAMO. Pode-se tomar como hipóteses que a assimetria de recursos entre o partido dominante no poder, a FRELIMO, e o maior partido da oposição, bem como os custos assimétricos de filiação à oposição, contribuiram para a radicalização da postura do maior partido da oposição, que se insurgiram militarmente para expressar a sua insatisfação. Dado ao facto dos militantes partidários que visam ocupar cargos públicos priorizarem a vitória nas eleições, valida-se a hipótese que os militantes da RENAMO que almejam tais cargos, tornaram-se mais sensíveis as vantagens dos recursos do partido FRELIMO, como denota-se em certos discursos feitos à imprensa. Mas por outro lado, se as vantagens dos recursos entre a FRELIMO e a RENAMO forem mais simétricas, os mesmos militantes da oposição poderão moderar suas posições. Devido ao facto do partido dominante possuir mais recursos que a oposição, o número de militantes da oposição, bem como da RENAMO, que almejam cargos públicos será menor. Porém, quando os recursos que os partidos dominantes possuem entram em declínio- geralmente em períodos de crises económicas, quando os Governos são coagidos a reduzir o tamanho do setor público, principal fonte de recursos para o partido dominante-, o número de militantes da oposição que almejam cargos públicos aumenta. Com o agravar da crise da dívida pública moçambicana, e consequente declínio de recursos do partido dominante, a proporção de militantes na oposição (em especial na RENAMO) que visam adquirir cargos públicos poderá aumentar. Mas como as vantagens detidas pelo partido dominante, a FRELIMO, ainda são maiores, a oposição continuará apresentando um número de votos mais baixo.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; conflict - civil war / conflito - guerra civil; conflict / conflito; ⛔ No DOI found

Social protection reform in Mozambique and the new basic social security strategy - Falange, Sergio; Pellerano, Luca (International Policy Centre for Inclusive Growth, 2016)
In the framework of efforts to fight extreme poverty and recognising the importance and need to protect the poor and vulnerable population, in 2007 Mozambique approved Law No. 4/2007 which structured social protection into three levels, including basic social security. In 2010 the first National Basic Social Security Strategy (ENSSB I) was approved for the period 2010–2014, including a set of old (e.g. the Basic Social Security Programme—PSSB) and new (e.g. the Productive Social Action Programme—PASP) non-contributory social protection programmes, all implemented by the National Institute for Social Action (INAS) under the policy guidance of the Ministry of Gender, Child and Social Action (MGCAS).
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Estratégia Nacional de Segurança Social Básica 2016-2024 - Governo de Moçambique (Governo de Moçambique, 2016)
a Estratégia Nacional de segurança social Básica (ENssB) 2016-2024 visa a materialização do Programa Quinquenal do governo 2015-2019, através da implementação de acções que concorrem para a redução da pobreza e da vulnerabilidade, assegurando que os resultados do crescimento da economia moçambicana beneficiem a todos os cidadãos, sobretudo os que vivem em situação de pobreza e de vulnerabilidade. A elaboração da presente Estratégia teve como base as metas definidas na Estratégia Nacional de Desenvolvimento 2015-2035, a Agenda 2063 da União Africana, os Objectivos de Desenvolvimento Sustentável, aprovados pelas Nações Unidas que, no seu conjunto, enfatizam a abordagem dinâmica e promocional da protecção social e o potencial dos instrumentos de segurança social básica para reforçar o capital humano, produtivo e social assim como a capacidade de resiliência dos agregados familiares e indivíduos mais vulneráveis. Esta estratégia pretende continuar com as acções levadas a cabo, desde a adopção da Lei de Protecção Social em 2007, para construir um sistema eficaz e eficiente de segurança social básica e apresenta uma abordagem integral para a protecção social dos grupos mais desfavorecidas da população moçambicana, definindo as linhas orientadoras para o reforço da sua capacidade de protecção contra os riscos sociais de modo que saiam da situação de vulnerabilidade numa base sustentável a longo prazo. A ENSSB 2016-2024 foi elaborada, considerando o perfil de vulnerabilidades e de riscos no país, as funções da segurança social básica e o diagnóstico da situação actual do sistema, apresentando os seguintes objectivos: 1) Reforçar o nível de consumo e a resiliência das camadas pobres e vulneráveis da população; 2) Contribuir para o desenvolvimento do capital humano, através da melhoria de nutrição e do acesso aos serviços básicos de saúde e educação das camadas pobres e vulneráveis da população; 3) Prevenir e responder aos riscos de violência, abuso, exploração, discriminação e exclusão social, através de serviços de acção social, e 4) Desenvolver a capacidade institucional para a implementação e coordenação do subsistema de segurança social básica. Para a operacionalização destes objectivos, a ENSSB 2016-2024 estrutura-se em quatro eixos de intervenção, nomeadamente: » Eixo 1: Reforço do consumo, da autonomia e da resiliência; » Eixo 2: Melhoria da nutrição e do acesso aos serviços de saúde e de educação; » Eixo 3: Prevenção e resposta aos riscos sociais; e » Eixo 4: Desenvolvimento institucional. Eixo 1: operacionaliza o primeiro objectivo da estratégia e engloba as acções que visam reforçar, no sistema de segurança social básica, as funções de compensação devido a velhice e incapacidade funcional, a redução da pobreza e da desigualdade social e a promoção da autonomia e resiliência das camadas pobres e vulneráveis da população. Prevê-se introduzir modificações no Programa Subsídio Social Básico para estabelecer os subsídios para a pessoa idosa e de incapacidade funcional. Através deste Eixo será expandido o actual Programa de Acção Social Produtiva (PASP) e reforçado o seu papel na promoção da autonomia e graduação dos seus beneficiários em situação de pobreza. Outro aspecto incluso no presente Eixo é o fortalecimento do papel da segurança social básica na resposta a choques. Eixo 2: focaliza-se nas acções que promovem o desenvolvimento do capital humano, através da melhoria da nutrição e do acesso aos serviços de saúde e educação (objectivo 2). Neste eixo estão enquadrados os subsídios para a criança. Eixo 3: diz respeito aos Serviços de Acção Social que visam prevenir e responder aos riscos sociais que afectam principalmente crianças, mulheres, pessoas idosas, pessoas com deficiência e pessoas afectadas pelo HIV e SIDA (objectivo 3). Eixo 4: Centra-se nas acções de desenvolvimento institucional (objectivo 4) requeridas para reforçar a capacidade de implementação dos primeiros três eixos a todos os níveis (central, provincial e distrital). Estão previstas na Estratégia acções para o reforço da coordenação intersectorial e a monitoria dos resultados da implementação da ENSSB 2016-2024, através do Conselho Nacional de Acção Social (CNAS). Espera-se que com a implementação da presente Estratégia sejam alcançados 3.352.515 beneficiários directos e um total de 8.274.789 beneficiários indirectos, devendo ser alocado um orçamento correspondente a 2.23% do PIB até 2024
Keywords: #Policy Document / Documento de Política; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; government policy / politica governamental; social protection / proteção social

The promotion of decentralisation and local governance in fragile contexts - Grävingholt, Jörn; von Haldenwang, Christian (Deutsches Institut für Entwicklungspolitik gGmbH, 2016)
The promotion of decentralisation and local governance has long since been an established part of bilateral and multilateral development cooperation. In the context of fragile statehood, however, this area of development cooperation is frequently faced with the general suspicion of encouraging separatism, exacerbating conflicts, and thereby promoting the disintegration of the state. At the same time, fragile contexts create demand for institutional solutions concerning the distribution of tasks, responsibilities, resources and political power between the various different levels of the state. This paper provides an overview of the challenges regarding support to decentralisation and local governance in fragile contexts. It discusses risks and opportunities, and develops suggestions on how development cooperation can better rise to the challenges surrounding the promotion of decentralisation in fragile states. Against this background the authors advocate an ambitious approach which understands the promotion of decentralisation as being a contribution to overcoming fragility and to the structural alleviation of conflict situations.
OCLC: 962061613
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

Mozambique Early Generation Seed Study - USAID (Scaling Seeds and Technologies Partnership in collaboration with The Rutgers University, 2016)
Seed systems in Mozambique There are three identified dominant seed systems in Mozambique, namely informal seed system (mainly farmer-saved seed), the intermediary (mainly administered by the NGOs and communitybased organizations) and the formal seed system that includes public sector and private sector (local and international seed companies). The farmer-saved and intermediary systems account for the bulk of seed volume transacted across the country (90%) focusing mainly on the local varieties. Although the adoption rate is relatively high for cassava, there is no vegetative seed certification system in place. There is no official sesame variety, despite an over three-fold increase in the last 12 years in terms of the total area allocated to this crop. Early generation seed systems by crop Six crops selected for the Mozambique EGS case study were maize (hybrid and OPV), rice, cowpea, groundnut, soybean and cassava
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura